Global urban environmental change drives adaptation in white clover - Santangelo, James S. (2022)
Urbanization transforms environments in ways that alter biological evolution. We examined whether urban environmental change drives parallel evolution by sampling 110,019 white clover plants from 6,169 populations in 160 cities globally. Plants were assayed for a Mendelian antiherbivore defence that also affects tolerance to abiotic stressors. Urban-rural gradients were associated with the evolution of clines in defence in 47% of cities throughout the world. Variation in the strength of clines was explained by environmental changes in drought stress and vegetation cover that varied among cities. Sequencing 2,074 genomes from 26 cities revealed that the evolution of urban-rural clines was best explained by adaptive evolution, but the degree of parallel adaptation varied among cities. Our results demonstrate that urbanization leads to adaptation at a global scale.